Effect of edible onion (Allium cepa L.) film on quality, sensory properties and shelf life of beef burger patties - Soares, Kallyne Sousa; Souza, Marthyna Pessoa; Silva-Filho, Edson C.; Barud, Hernane Silva; Ribeiro, Clóvis Augusto [UNESP]; Santos, Diógenes Dias; Rocha, Karla Nayalle Souza; de Moura, José Fabio Paulino; Oliveira, Ronaldo Lopes; Bezerra, Leilson Rocha (MDPI, 2021)
The production of edible film from onion (Allium cepa L.) to be applied as packaging is attractive, due to its chemical properties and biodegradable characteristics. Thus, we tested the hypothesis that edible onion film can positively influence the sensory properties, quality and increasing shelf life of beef burgers patties. The experiment was designed in a 4 × 2 factorial scheme, with two treatments (beef burgers patties with or without edible onion film) at an interval of four storage times (0, 3, 6 and 9 days) at 4◦ C. The uncoated burger patties (control) suffered the most intense color modifications during the storage (p < 0.05). The luminosity index was higher (p < 0.05) in the control at all storage times, except at day 6, and redness, yellowness and chrome were higher (p < 0.05) in the edible onion film patties at all storage times. The pH of the beef burger patties was lower (p < 0.05) at all storage times when the edible onion film was applied. For the texture profile, only the chewiness was affected, as the inclusion of the edible onion film improved the chewing of the beef burgers patties over the storage time (p < 0.05). Additionally, there was an inhibition of the microbial growth of mesophiles and psychrophiles with the application of the edible onion film in beef burgers patties. The use of edible onion film improved the perception of panelists for the variables texture, color, flavor, odor and overall appearance, and increased the preference of panelists. The edible onion film is recommended for preserving beef burgers patties, as it delays the proliferation of unwanted microorganisms, stabilizes and improves the color parameters and sensory attributes, and increases the overall acceptance of the consumer.
Keywords: Antimicrobial; Beef burgers patties; Edible coating; Lipid oxidation; Texture